THE USE OF PEER-ASSISTED LEARNING STRATEGY IN DEVELOPING SCHOOL LEARNERS’ COMMUNICATIVE SKILLS - Kerishbay A; Kudaibergenova M.R; Anesova A.Zh. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Recently, special importance has been attached to the communicative education of schoolchildren, since success in speech development determines the effectiveness of mastering other school disciplines, creates prerequisites for active and meaningful participation in public life, provides children with the skills of speech behavior necessary in their personal life, and a culture of speech development.